Two new species of shrub frogs (Rhacophoridae: Philautus) from the lowlands of Sri Lanka - Meegaskumbura, Madhava; Manamendra-Arachchi, Kelum; Pethiyagoda, Rohan (Zootaxa, 2009)
Two new species of Sri Lankan frogs of the genus Philautus are described. Species diagnoses are based on morphology, morphometrics and mitochondrial DNA sequence data. Philautus tanu sp. nov. inhabits shrubs in open areas of the lowland wet zone, while P. singu sp. nov. is found on shrubs in the understory of lowland and mid-elevation rainforests. These descriptions bring the total number of valid Sri Lankan Philautus to 65 species, of which 46 are extant.